Sowing date effects on cowpea cultivars as a second crop in southeastern Brazil - Matoso, Aline O. [UNESP]; Soratto, Rogério P. [UNESP]; Guarnieri, Franciele [UNESP]; Costa, Nídia R. [UNESP]; Abrahão, Rafael C. [UNESP]; Tirabassi, Luís H. [UNESP] (Wiley, 2018)
In southeastern Brazil, there has been increasing interest in cowpea [Vigna unguiculata (L.) Walp.] cultivation as a second crop. A three-year study was conducted to evaluate the growth, seed yield, and seed protein of cowpea cultivars (BRS Cauamé, BRS Guariba, BRS Itaim, BRS Novaera, BRS Potengi, BRS Tumucumaque, and BRS Xiquexique) as affected by sowing date (from early February to late April) in Botucatu, Brazil. Delay in sowing, especially after early March, delayed the emergence and flowering and increased the cycle of the cowpea cultivars. On average, each day of sowing delay increased the crop cycle by 0.82 d because of the decreasing temperature. The delay in sowing from late March drastically reduced the aboveground dry matter biomass, numbers of lateral branches and pods per plant, 100-seed weight, and seed yield of cowpea cultivars. There was great variation in the seed yield across growing seasons, but the earliest sowing date (early February) resulted in the greatest seed yields, which could reach up to 2746 kg ha–1. Sowing dates until early March provided sustainable seed yields (on average >800 kg ha–1). Cultivar ranking varied across sowing dates and growing seasons, but with sowing dates from early February to early March, the cultivars BRS Cauamé, BRS Guariba, BRS Novaera, and BRS Potengi were the most productive. Sowing dates later than early March also reduced the crude protein content in the seeds of cowpea cultivars. Cowpea has potential as an alternative second crop in southeastern Brazil since it can be sown until early March.